The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1365-2214.2008.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Transition to adult care: experiences and expectations of adolescents with a chronic illness

Abstract: Subspecialty paediatric providers should anticipate common fears and concerns of adolescents and discuss the benefits of transfer to adult-oriented care. Further evaluation of existing transition programmes is an area for future study and is necessary for improvement of the continuum of care for adolescents with chronic medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 15 publications
(24 reference statements)
2
162
0
3
Order By: Relevance
“…Transitional care in rheumatology is widely advocated and has been shown to improve health-related quality of life (29,31). In our review, only 3 qualitative studies have elicited views from adolescents on transition (32)(33)(34). Future work is needed that actively involves patients during the whole process of transition and to ensure that perspectives, priorities, and concerns are addressed in order to improve medical and quality of life outcomes in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Transitional care in rheumatology is widely advocated and has been shown to improve health-related quality of life (29,31). In our review, only 3 qualitative studies have elicited views from adolescents on transition (32)(33)(34). Future work is needed that actively involves patients during the whole process of transition and to ensure that perspectives, priorities, and concerns are addressed in order to improve medical and quality of life outcomes in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The adult-care provider might have little knowledge about the transferred patient's condition, making the young adult worried about not receiving the right level of care (Tuchman et al, 2008). They tired of retelling their life story and described the transition as being in no man's land (Anthony et al, 2009, Patterson and Lanier, 1999, Valenzuela et al, 2011.…”
Section: )mentioning
confidence: 99%
“…Without timely follow-up to check whether the patient experienced complications or problems with the transition, patients might become lost in the health care system. Studies have shown that patients with long-term special healthcare needs are more vulnerable to abrupt environmental changes, including changes in the healthcare setting [16] and concern about building new relationships with adult health care providers [17]. When patients are not transferred appropriately or are transferred abruptly, they may experience discontinuation of medical care and emotional care which may exacerbate preexisting health conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The primary concern of young adults regarded their ability to pay and acceptance by adult care providers [18]. Studies have identified a lack of information on transition, fear of departing from their familiar healthcare provider [13] and embarking on a relationship with a new provider [17] as major concerns on transition to adult care. Once young patients were moved to adult care successfully, they acknowledged benefits of the adultoriented system even though most young patients were concerned about adaptation prior to transition [17].…”
Section: Resultsmentioning
confidence: 99%